2023
DOI: 10.3171/2022.5.jns22411
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance–guided focused ultrasound thalamotomy restored distinctive resting-state networks in patients with essential tremor

Abstract: OBJECTIVE Magnetic resonance–guided focused ultrasound (MRgFUS) thalamotomy ameliorates symptoms in patients with essential tremor (ET). How this treatment affects canonical brain networks has not been elucidated. The purpose of this study was to clarify changes of brain networks after MRgFUS thalamotomy in ET patients by analyzing resting-state networks (RSNs). METHODS Fifteen patients with ET were included in this study. Left MRgFUS thalamotomy was performed in all cases, and MR images, including resting-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Furthermore, a study described decreased FC within a SMN, visual network, and visuo-spatial network. ( Kato et al, 2022 ) In orthostatic tremor, findings similar to a study done in ET patients were reported, namely increased connectivity in a DMN and CCN, and decreased connectivity in a cerebellar and SMN. ( Benito-Leon et al, 2016 ).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Furthermore, a study described decreased FC within a SMN, visual network, and visuo-spatial network. ( Kato et al, 2022 ) In orthostatic tremor, findings similar to a study done in ET patients were reported, namely increased connectivity in a DMN and CCN, and decreased connectivity in a cerebellar and SMN. ( Benito-Leon et al, 2016 ).…”
Section: Resultssupporting
confidence: 63%
“…The 51 included articles on tremor concerned tremor-dominant Parkinson’s disease (TDPD; n = 28), essential tremor (ET; n = 21), orthostatic tremor (n = 2), and primary writing tremor (n = 1). ( Bagarinao et al, 2022 , Basaia et al, 2022 , Benito-Leon et al, 2015 , Benito-Leon et al, 2016 , Benito-Leon et al, 2019 , Chen et al, 2015 , Chen et al, 2019 , Dirkx et al, 2017 , Dirkx et al, 2019 , Duan et al, 2021 , Fang et al, 2013 , Fang et al, 2015 , Fang et al, 2016 , Gallea et al, 2015 , Gallea et al, 2016 , Gu et al, 2017 , Helmich et al, 2011 , Hou et al, 2018 , Hu et al, 2015 , Hu et al, 2017 , Hu et al, 2019 , Jiang et al, 2016 , Karunanayaka et al, 2016 , Kato et al, 2022 , Lenka et al, 2017 , Lenka et al, 2017 , Li et al, 2018 , Li et al, 2020 , Li et al, 2021 , Li et al, 2021 , Ma et al, 2015 , Ma et al, 2017 , Mueller et al, 2017 , Nicoletti et al, 2020 , Nigro et al, 2019 , Popa et al, 2013 , Quarantelli et al, 2022 , Tikoo et al, 2020 , Tuleasca et al, 2018 , Tuleasca et al, 2020 , Vervoort et al, 2016 , Wang et al, 2016 , Wang et al, 2018 , Wang et al, 2021 , Wen et al, 2016 , Yin et al, 2016 , Zhang et al, 2015 , Zhang et al, 2015 , Zhang et al, 2015 , Zhang et al, 2016 , Zhu et al, 2021 ) The number of patients per study ranged from 10 to 99.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed differences in functional connectivity after focused ultrasound thalamotomy. For example, functional connectivity was shown to increase between the thalamus and premotor cortex, 40 and within the sensorimotor and visuospatial networks 41 after, as compared to before, thalamotomy. Differences in functional connectivity following thalamotomy might be related to distinct mechanisms of action for lesioning as compared to electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The full study selection process for inclusion in this analysis is detailed in the PRISMA flow diagram (Figure 1). Fifteen studies (n = 464) with FUS-T [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and 3 studies (n = 62) with SRS-T [41][42][43] met inclusion criteria for pre-thalamotomy vs post-thalamotomy efficacy analyses. The weighted average follow-up times were 10.3 months and 14.1 months for FUS-T and SRS-T groups, respectively.…”
Section: Patient Demographics Of Included Studies For Efficacy Compar...mentioning
confidence: 99%